Gambaran Self-Concept pada Mahasiswi Fakultas Psikologi Universitas Padjadjaran yang Pernah Mengalami Body Shame - Ristianto, Putri Shania Maulidia; Jatnika, Ratna (Penerbit Goodwood, 2023)
Purpose: This research aims to investigate the self-concept of female students who have experienced body shame. Methodology: This study utilizes a non-experimental design with a quantitative descriptive method. The respondents in this research comprise 105 female students from the Faculty of Psychology at Universitas Padjadjaran who have experienced body shame, selected using quota sampling. The measurement instruments include the Tennessee Self Concept Scale by Fitts and the body shame subscale, which is part of the Objectified Body Consciousness Scale. Results/findings: The results of this study indicate that the majority of female students from the Faculty of Psychology at Universitas Padjadjaran who have experienced body shame possess a positive self-concept. Furthermore, it was also found that body shame categorized as moderate and high significantly differs in its impact on self-concept. Conclusions: The majority of female students who have experienced body shame are able to accept themselves, face problems with confidence, and improve without feeling inferior. Limitations: This study employs a measuring instrument with marginal fit validity, indicating limitations in its ability to comprehensively measure a construct. Contribution: This research provides valuable information about the importance of fostering a positive self-concept in female students and also offers insights into the impact of body shame on the self-concept of female students.